Halal Slaughterhouse Certification: The Comparison between Two Halal Certification Bodies - Sherly Artadita; Yuliani Dwi Lestari (Bina Nusantara University, 2019)
This research aimed to provide information regarding the process and requirement of halal slaughterhouse certification implemented in halal certification bodies archival comparison research strategy by using the secondary data. It usedt he comparison of halal slaughterhouse certification process and requirement were conducted between two halal certification bodies, those were Lembaga Pengkajian Pangan, Obat-obatan, dan Kosmetika Majelis Ulama Indonesia (LPPOM MUI - The Assessment Institute for Foods, Drugs and Cosmetics Majelis Ulama Indonesia) and Jabatan Kemajuan Islam Malaysia (JAKIM - Department of Islamic Development Malaysia). From the comparative analysis, the result shows that certification processes of LPPOM MUI and JAKIM are similar with slight differences. There are four main activities during the certification process in both halal certification bodies, namely application process, payment process, audit process, and certificate issuance/decision process. The criteria set by both halal certification bodies, in general, are similar. Those are classified into eight categories, although there are slight differences. The eight categories are halal control/assurance system, human resource, permitted animal, production facilities, storage and transportation, packaging and labeling, slaughtering process, and stunning.